The Effect of Service Quality on Purchase Intention with Mediating Role of Store Image - Aamir Abbas; Mahmood A. Hussain Akbar; Mohd Helmi Ali (International Journal of Supply Chain Management, 2020)
This study emphasizes to measure the effect of service quality on purchase intention with mediating role of store image. The study majorly focused on paint brands available at stores of Manama, Bahrain. Reliability of data, descriptive analysis and Pearson correlation matrix was calculated by using SPSS. The relationship among study variables is tested trough structural equation modeling (SEM) by using AMOS 24. Results highlighted that there is significant and positive relation between service quality and purchase intention of private label paint brands. Moreover, it was found that store image mediates the relationship between service quality and purchase intention of private label paint brands.